Ochrona zdrowia jako element polityki publicznej - Barańska, Marzena (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2013)
Public health is strictly related to health policy, since political decisions determine the selection of priorities and the distribution of assets. Health, perceived in this way, is protected by global activities, and not only by a given country or region. Health is a significant element among the tasks handled by public authorities. A con- sequence of these activities is ensuring medical care by means of developing the right apparatus and mechanisms of solutions allowing for common access to treat- ments offered.
Protection of health as an element of public policy